Stable isotopes as indicators of ecological change. - Dawson, Todd E., 1955-; Siegwolf, Rolf T. W. (Terrestrial ecology., 2007)
* Provides researchers with ground-breaking data on how to predict the terrestrial ecosystems response to the ongoing rapid alterations * Reveals how ecosystems have responded to environmental and biotic fluctuations in the past * Includes examples from research by a wide range of biological and physical scientists who are using isotopic records to both detect and interpret environmental change.